Determinan Kecenderungan Fraud Accounting dalam Pengelolaan Keuangan Desa dengan Moralitas Inndividu sebagai Pemoderasi - Devi Adhana; Saiful Muchlis; Nur Rahma Sari (Indonesian Journal of Taxation and Accounting, 2024)
The purpose of this study was to determine how the effect of individual morality as a moderating variable of internal control, compensation suitability and organizational culture on the tendency of fraud accounting in the Village Government of Donri-Donri District, Soppeng Regency.In this study using a sample of 65 respondents with total sampling technique. The data used in this study are primary data, namely data collected by distributing questionnaires that have been previously prepared to be filled in directly by respondents. The data analysis technique used in this study is multiple linear regression analysis and absolute value difference analysis. The results of this study indicate that internal control, compensation suitability and organizational culture have a negative effect on the tendency of fraud accounting. Moderating variables, namely individual morality, are able to moderate the relationship between organizational culture and the tendency of fraud accounting, but are unable to moderate the relationship between internal control and compensation suitability on the tendency of fraud accounting. The implication of this research is that the village apparatus should be transparent about the budget realization report every year, as well as the budget realization report. The results of this study are expected to help identify risks and early indications of fraud in anticipating possible fraud that occurs, especially in the government sector. Meanwhile, future researchers are expected to expand the scope by exploring other factors that influence the tendency of fraud accounting in financial management.